Evaluation of acute and sub acute toxicities of leaf extract of Caesalpinia Bonducella (L) Flem - KAVITHA SAGAR; G M VIDYASAGAR (International Journal of Pharma and Bio Sciences, 2010)
The acute and sub acute toxicity studies of ethyl acetate extract of Caesalpinia bonducella leaves in albino mice were investigated. Various doses of ethyl acetate leaf extract from 800 to 2000 mg/kg body weight were administered orally to the test groups of mice, while distilled water was given to the control group to evaluate the toxicity in mice after ingestion of the extract for one day (acute model) and for 15 days (sub acute model). The behavioral response profile of the treated mice was also evaluated along with other parameters such as, body weight, absolute and relative weight of various organs. Biochemical, hematological and histopathological parameters were analyzed in order to study the time-dependent effect and correlation of the extract. The results indicated that LD50 of the extract is higher than 2000 mg/kg and no changes were observed in any behavioral parameters in mice. Body weight of mice increased along with the time in sub acute model. The biochemical (total protein, DNA, RNA, alkaline phosphatase, acid phosphatase, cholesterol, and carbohydrate) and hematological parameters (total RBC and WBC) and histopathological studies of liver, heart, lung and kidney indicated either no or less alteration in the treated group. However, a slight change in liver cellular architecture with hydropic changes in the epithelium, congested sinusoids and dilation of central vein was observed in liver of test animal.